A Study of the Perception of the Institutional Factors That Influence the Academic Performance of Students of the Distance State University of Costa Rica - Echeverría-Ramírez, José Alejandro (2021)
Objective. To know the student perception about the influence of various institutional factors on academic performance, in a sample of students from the Distance State University  of Costa Rica (UNED), in order to contribute with a scientific analysis in the distance education training processes. Methodology. The study was conducted from a predominantly quantitative research approach. The student sample was made up of 418 UNED students from these geographical regions: Chorotega, Huertar Norte, Atlántica, Central, Brunca, and Central Pacific, where the university has regional campuses. Analysis of results. The data collection was carried out through a structured survey with a Likert scale format with the following five levels of selection: it affects me much; it affects me little; it does not affect me or benefit me; it benefits me little: and it benefits me much. For the statistical analysis, the SPSS program was used. This article presents the results concerning the student’s perception of the influence of institutional factors on academic performance. Conclusions. According to the student body’s perception, institutional factors, such as the type of enrollment system (web-enrollment), the platform used as a student environment, and distance study system, do not influence or affect academic performance at UNED. The institutional factor of availability of open courses per semester negatively influences the academic performance of UNED students.